Determinants of First-Trimester Antenatal Care Delay in Indonesia's Disadvantaged Regions: A Cross-Sectional Study of Socioeconomic Barriers in South Tapanuli - Suryani, Elvi; Fatimah, Fatimah; Siregar, Rahmah Juliani; Harahap, Maryam Latifah (International Journal of Public Health Excellence (IJPHE), 2025)
Background: Delayed access to first-trimester Antenatal Care (ANC) among pregnant women in underdeveloped, frontier, and outermost (3T) regions is a significant public health issue, as it increases the risk of pregnancy complications. This study aims to analyze the socio-economic determinants associated with delayed ANC access in South Tapanuli, a 3T region in Indonesia. Methods: This cross-sectional study involved 250 pregnant women selected through purposive sampling in South Tapanuli. Data were collected through structured interviews using a questionnaire covering socio-demographic variables (education, income, occupation, distance to health facilities) and ANC practices. Statistical analysis employed chi-square tests and logistic regression to identify dominant factors influencing ANC delay. Results: A total of 62.4% of respondents delayed accessing ANC in the first trimester. Significant socio-economic factors associated with delayed ANC included low income (OR=3.21; 95% CI: 1.87-5.49), low education (OR=2.45; 95% CI: 1.42-4.22), distance to health facilities >10 km (OR=4.12; 95% CI: 2.34-7.25), and lack of knowledge about ANC importance (OR=2.89; 95% CI: 1.65-5.07). Conclusion: Socio-economic factors such as income, education, geographic access, and maternal knowledge significantly influence delayed ANC access in 3T regions. Community-based interventions and equitable health service policies are needed to improve first-trimester ANC coverage.